OBTAINING ASEPTIC CULTURE IN VITRO OF RHODIOLA SEMENOWII L. FROM VARIOUS TYPES OF EXPLANTS - Raizer, O.; Tagimanova , D.; Baltabaeva, K.; Khapilina , O. (Eurasian Journal of Applied Biotechnology, 2024)
In vitro cultivation of callus cells allows for the stable production of secondary metabolites, being an alternative to the use of medicinal plant biomass from natural populations. Standardization of cultivation protocols and technological processes for the synthesis of secondary metabolites in vitro conditions determines significant interest in the use of tissue culture methods (PTC – Plant Tissue Culture). The aim of the study was to obtain an aseptic culture of Rhodiola semenowii in vitro from various types of explants, as well as the effect of the hormonal composition of the nutrient medium on the induction of callusogenesis in the culture of isolated organs of R. semenowii. As a result of the research, the optimal mode of obtaining R. semenovii aseptic cultures from various explants was determined. It has been shown that the use of 70% EtOH in combination with 0.01% HgCl2 or 20% NaClO makes it possible to obtain aseptic cultures from any type of R. semenovii explants. It has been established that the type of explant is R. semenovii influenced both the frequency of callus formation and the beginning of its formation. The least optimal types of R. semenovii explants are stem and rhizome segments, the frequency of callusogenesis varied from 5.8% to 75.6%. The induction of callusogenesis also depended on the hormonal composition of the nutrient medium: the highest percentage of callus formation in all types of explants was on media containing 0.5mg L−1 thidiazuron (TDZ) + 1.0 mg L−1 1-naphthaleneacetic acid (NAA) and 0.5mg L−12,4D + 2.0 mg L−1 6-Benzylaminopurine (BAP).